2018
DOI: 10.1021/acs.est.8b04673
|View full text |Cite
|
Sign up to set email alerts
|

Organic Carbon Amendments Affect the Chemodiversity of Soil Dissolved Organic Matter and Its Associations with Soil Microbial Communities

Abstract: Organic carbon amendments affect the chemodiversity of soil dissolved organic matter and its associations with soil microbial communities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(89 citation statements)
references
References 63 publications
3
80
0
Order By: Relevance
“…Aliphatic and low-polar compounds are preferentially dissolved in the soil solution, whereas unsaturated, aromatic and highly polar compounds tend to be adsorbed onto soil particles (Huang et al, 2019). Furthermore, total soil nitrogen and organic carbon content increased by long-term fertilization is influencing the activity of the soil bacterial community, which in turn will affect soil DOM composition (Li et al, 2019). In our study even, the impact of fertilization was controlled by soil texture.…”
Section: Composition Of Leached Organic Mattermentioning
confidence: 54%
See 2 more Smart Citations
“…Aliphatic and low-polar compounds are preferentially dissolved in the soil solution, whereas unsaturated, aromatic and highly polar compounds tend to be adsorbed onto soil particles (Huang et al, 2019). Furthermore, total soil nitrogen and organic carbon content increased by long-term fertilization is influencing the activity of the soil bacterial community, which in turn will affect soil DOM composition (Li et al, 2019). In our study even, the impact of fertilization was controlled by soil texture.…”
Section: Composition Of Leached Organic Mattermentioning
confidence: 54%
“…Ferrari et al (2011) suggested that long-term organic fertilization led to an enrichment of organic N, thus enhancing the lignin decomposition of crop residues. However, mineral fertilization resulted in an enrichment of hydrophilic compounds (McDowell et al, 2004) or enhanced labile organic compounds, such as carbohydrates, amino sugars, and proteins (Li et al, 2019). In a 56-days incubation experiment, mineral fertilization with NH 4 Cl accelerated microbial turnover of labile organic carbon, while the decomposition of recalcitrant soil organic matter declined (Zang et al, 2017).…”
Section: Composition Of Leached Organic Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by Kallenbach et al (2019), a mixture of crop residues of different C:N ratios could therefore achieve a more diverse microbial community comprising organisms fulfilling niches of both high and low inherent CUE windows, and may 85 enable all species to operate at their maximum CUE. Other authors have also suggested the possibility of manipulating the functionality of the soil microbial community with soil amendments, such as Li et al (2019) who report that microbes in a eutrophic system are stimulated by organic carbon amendments and oligotrophic microbes are stimulated by chemical fertilisers. Studies have also demonstrated that changes in tree litter diversity affect both fungal and bacterial diversity (Otsing et al, 2018;Santonja et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly more evidence is emerging that SOM accumulation is primarily derived from the production of microbial residues (Ludwig et al, 2015;Simpson et al, 2007), and this microbially derived SOM seems to be produced in the early stages of plant residue decomposition (Cotrufo et al, 2015). Microbial carbon use efficiency (CUE) describes a functional trait of microbes that refers to the fraction of carbon assimilated from organic matter additions to the soil system compared to C losses to the atmosphere via microbial respiration (Allison et al, 2010).…”
mentioning
confidence: 99%